Kakovostna zgradba bukovih sestojev in pojavljanje rdečega srca na rastišču Isopyro-Fagetum KOŠ. 62 - Meterc, Gregor (Gozdarski vestnik, 2010)
This paper analyses the quality of beech stands on sites classified into Isopyro-Fagetum association. Analysis showed rather high frequency of stem defects, low situated covered knot on tree stems, frequent red heartwood appearance and consequently an unfavorable assortment structure. The normal type prevails among the red heartwood types and it is followed by the abnormaltype. Rottenness occurs often as well.
Keywords: forestry; gozdarstvo; bukovi sestoji; kakovost debel; sortimentna struktura; rdeče srce; bukev; Fagus sylvatica L.